FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS MANAGEMENT DISEPUTAR RIGHT ISSUE DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Rima Melati; Suyanto Suyanto; Gustin Padwa Sari (Jurnal Akuntansi AKTIVA, 2020)
This study aims to analyze the factors that influence earnings management around the right issue,namely (1) information asymmetry, (2) capital structure and (3) financial performance. The objects in this studyare companies listed on the Indonesia Stock Exchange in 2016-2018. The population of this research is 666companies. The sample selection technique used is Purposive Sampling so as to obtain a sample of 37companies that commit rights issues between 2016-2018. This study uses a quantitative approach. Data wereanalyzed by using SPSS version 22. The results of this study indicate that: (1) Information asymmetry has noeffect on earnings management around the rights issue. (2) Capital structure has a negative effect on earningsmanagement around the right issue. (3) Financial performance has a positive effect on earnings managementaround the right issue. (4) Audit quality is able to moderate the information asymmetry relationship to earningsmanagement around the rights issue. (5) Audit quality is able to moderate the relationship of capital structure toearnings management around the right issue. (6) Audit quality is able to moderate the relationship betweenfinancial performance and earnings management around the right issue.